2016
DOI: 10.1007/978-3-319-32521-7
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Surface Passivation: Understanding the Si-Al2O3 Interface

Abstract: High-efficiency crystalline silicon solar cells must suppress recombination at their p-type surfaces. Thin-film, amorphous aluminium oxide (Al 2 O 3) has been shown to provide very effective passivation of such surfaces, assisted by its negative fixed charge. However, many details of Al 2 O 3 passivation remain poorly understood. Furthermore, conventional means of depositing passivating Al 2 O 3 are too slow or too expensive to be suitable for high-volume commercial production. This thesis addresses these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 193 publications
(455 reference statements)
1
33
1
Order By: Relevance
“…One of the major issues is the formation of positive surface charge due to both the mechanisms. 10,18 The surface charge leads to band-bending at the surface of the semiconductor, the extent of which is described by the surface potential 61 (∼690 meV for our case). The presence of the surface potential and the formation of 2DEG are illustrated in the form energy band diagram in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…One of the major issues is the formation of positive surface charge due to both the mechanisms. 10,18 The surface charge leads to band-bending at the surface of the semiconductor, the extent of which is described by the surface potential 61 (∼690 meV for our case). The presence of the surface potential and the formation of 2DEG are illustrated in the form energy band diagram in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The need for fast industrial methods has driven research into new deposition methods for AlO x . Most recently, Black produced a comprehensive study of AlO x films using atmospheric pressure chemical vapour deposition (APCVD). He demonstrated that extremely high‐quality passivation can be achieved by a high‐throughput and industrially compatible method.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…The lower charge trap density and longer carrier recombination lifetime of samples with lead sulfate top layers indicate that the reaction of sulfate and phosphate ions with defective perovskite surface reduces the surface defect density, in addition to the charge compensation effect of these ions. The wide-bandgap lead oxysalt layer should also contribute to the reduced surface charge recombination rate, similar to the passivation of silicon by oxides (26).…”
mentioning
confidence: 99%